Side-edge dual-band MIMO antenna system for 5G cellular devices - Imran, Mohd Ibrahim; Savcı, Hüseyin Şerif; Hassan Kiani, Saad; Rafique, Umair; Alsunaydih, Fahad N.; Alsaleem, Fahd; Alhassoon, Khaled; Mostafa, Hala (Elsevier GmbH, 2024)
An eight-element multiple-input multiple-output (MIMO) antenna system is presented for two distinct 5G allocated bands, i.e., 3.5 and 5.2 GHz. The MIMO radiating elements are printed on each side of the mobile phone chassis, having dimensions of 150 × 7 mm2, while the microstrip feeding lines fed through a coaxial connector are printed on the main board, having dimensions of 150 × 75 mm2. The single element of the MIMO antenna system consists of a modified slotted rectangular patch radiator. One slot is composed of a hybrid shape (which consists of both T- and L-shaped patterns), and the second one is a typical inverted L-shaped slot. The placement of slots generated two different current paths, which led to dual-band response at 3.5 and 5.2 GHz. In the MIMO configuration, the arrangement of radiating elements ensures pattern diversity characteristics, which are useful for MIMO systems. Furthermore, the MIMO antenna system offers a minimum isolation of 13.5 and 21.5 dB at 3.5 and 5.2 GHz, respectively. From the results, it is also observed that the radiating elements offer a radiation efficiency of ≥70% at 3.5 GHz, while at 5.2 GHz, the radiation efficiency is noted to be >55% with acceptable gain. A comprehensive analysis of key performance parameters, e.g., envelope correlation coefficient (ECC), mean effective gain (MEG), and channel capacity (CC), was conducted, and it is noted that the proposed MIMO antenna system exhibits an ECC of less than 0.015, MEG of < −3 dB, and CC of 39.5 bps/Hz. In addition, the specific absorption rate (SAR) analysis of the proposed MIMO antenna was conducted and observed a value of 1.35 and 1.05 W/Kg at 3.5 and 5.2 GHz, respectively. To verify the computed results, a prototype of the proposed MIMO antenna was fabricated and subjected to thorough measurements. It was observed that the measured results satisfied the simulated data and aligned excellently with the measured data. Based on the performance of the proposed MIMO antenna, it became evident that the MIMO antenna structure can be used as a potential candidate for future fifth-generation (5G)-enabled smart phones.